197. Bridging the Divide Between Antimicrobial Stewardship and Surgical Services: Successful Use of Handshake Stewardship with Hepato-Pancreato-Biliary Surgical Services in Adult Patients at a Large Academic Medical Center. (31st December 2020) - Meredith, Jacqueline; Roshdy, Danya; Jaffa, Rupal K; Medaris, Leigh A; Aviles, Cesar; Cochran, Allyson; Fischer, Kristin; Shastry, Vivek; Davidson, Lisa
Abstract: Background: Handshake stewardship has displayed promise in engaging providers in the pediatric population but literature in adults are lacking. Face-to-face interactions are proposed to improve antibiotic stewardship (ASP) efforts in challenging services that have low ASP acceptance and commonly utilize broad-spectrum antibiotics (BSA) such as Hepato-Pancreato-Biliary surgical services (HPBSS). Methods: Handshake stewardship was initiated by the Antimicrobial Support Network (ASN) with the HPBSS at the Carolinas Medical Center in January 2019. In-person rounding was completed. Treatment algorithms were created to assist in standardizing antibiotic selection and de-escalation for common HPB infections. To evaluate the impact of handshake stewardship, we assessed antimicrobial utilization of BSA by measuring days of therapy (DOT) per 1000 patient days (PD), comparing the pre- (Jan – Dec 2018) and post-intervention period (Jan – Dec 2019). ASN intervention acceptance rates and rates of hospital-acquired (HA) carbapenem-resistant Enterobacterales (CRE) infections/colonization and C. difficile infections (CDI) were also collected. Results: After implementation of handshake stewardship, antipseudomonal use decreased significantly by 32.5 DOT/1000 PD as compared to the pre-intervention period (174.4 vs 141.9 DOT/1000 PD, p = 0.04). A numeric decrease in carbapenem use was also observed (21.7 vs 57.5 DOT/1000 PD, p = 0.275). ASN intervention acceptance rates significantly increased by 31% (p < 0.01). HA-CRE infections, CRE colonization and CDI decreased by 87.7%, 66% and 38.8%, respectively (p = ns). Figure 1: HPB Antibiotic Utilization FIgure 2: ASN Intervention Rates with HPB Table 1. Rates of CRE and C. difficile Infections Conclusion: Use of handshake stewardship assisted in reducing BSA use, improving provider acceptance of ASN interventions and decreasing HA-infection rates. Based on these findings, handshake stewardship may be useful in services that display challenges in implementing ASP due to their complex patient populations, such as HPBSS. Disclosures: All Authors : No reported disclosures